2011
DOI: 10.1007/s10096-011-1400-1
|View full text |Cite
|
Sign up to set email alerts
|

Antistaphylococcal activity of Inula helenium L. root essential oil: eudesmane sesquiterpene lactones induce cell membrane damage

Abstract: The purpose of this study was to investigate the inhibitory/bactericidal activity and cell membrane effects of the hydrodistilled essential oil of Inula helenium L. roots against Staphylococcus aureus. Additionally, detailed chemical investigation was done in order to pinpoint the most active oil constituents and also the parts of these molecules responsible for their antimicrobial effect. The minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) were determined using the broth mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
53
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(56 citation statements)
references
References 24 publications
2
53
0
1
Order By: Relevance
“…Essential oils from Litsea cubeba contain fungicidal and antibacterial terpenoids [42, 43]. Sesquiterpene lactones from Inula helenium root essential oil exhibited antistaphylococcal activity [44]. …”
Section: Introductionmentioning
confidence: 99%
“…Essential oils from Litsea cubeba contain fungicidal and antibacterial terpenoids [42, 43]. Sesquiterpene lactones from Inula helenium root essential oil exhibited antistaphylococcal activity [44]. …”
Section: Introductionmentioning
confidence: 99%
“…Alantolactone (AL) (PubChem CID: 72724), as an active ingredient, has mainly been isolated from I. helenium L. plants Khan et al, 2012;Lim et al, 2007). AL shows various biological effects, including anthelmintic, antifungal (Tan et al, 1998;Tripathi et al, 1988), anti-inflammatory (Chun et al, 2012;Schmidt et al, 2002), antimicrobial (Stojanovic-Radic et al, 2012;Xin et al, 2008), and anti-proliferative effects on several cancer cell lines, such as prostate, ovary, colon, and leukemia (Konishi et al, 2002;Pal et al, 2010). However, most studies pay attention to pharmacological effects of AL and no study of its effects on CYPs has been conducted.…”
Section: Q4mentioning
confidence: 99%
“…Current literature shows that alantolactone and isoalantolactone possess various antimicrobial [3], antiinflammatory [4], and antitumor activities [5][6][7][8][9][10] both in vivo and in vitro. A recent study done by the team revealed that alantolactone and isoalantolactone could significantly relieve irritable bowel syndrome (IBS) by regulating neurotransmitters, gastrointestinal hormones, and intestine propulsive movement.…”
Section: Introductionmentioning
confidence: 99%